2015
DOI: 10.5455/njppp.2015.5.2810201415
|View full text |Cite
|
Sign up to set email alerts
|

A study of mental distress in medical students

Abstract: ||ABSTRACT Background: Mental distress is defined as unpleasant mental or emotional state, often impairing one's ability to cope with day-to-day living. The undergraduate medical training is a stressful period and medical students undergo tremendous stress during various stages of the MBBS course. Aims and Objective: The objective was to study the prevalence of mental distress among the undergraduate students of medical college and to find out the correlation between mental distress and different explanatory v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…In addition, the results of this study showed that the students’ academic year was significantly associated with stress. Similar findings were reported in studies conducted in Punjab, India, and Southern Ethiopia in which the likelihood of developing stress became lower as the students advanced in their years of study [ 42 , 43 ]. A possible reason for this would be the self-adjustment to face the challenges encountered by the junior freshmen in terms of the new environment and academic challenges besides separation from family members and friends.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the results of this study showed that the students’ academic year was significantly associated with stress. Similar findings were reported in studies conducted in Punjab, India, and Southern Ethiopia in which the likelihood of developing stress became lower as the students advanced in their years of study [ 42 , 43 ]. A possible reason for this would be the self-adjustment to face the challenges encountered by the junior freshmen in terms of the new environment and academic challenges besides separation from family members and friends.…”
Section: Discussionsupporting
confidence: 86%
“…43 Unlike other previous studies; year of study, scoring lower grades and having financial problems statistically has no significant association with mental distress. [23][24][25]44 This can be because of the variation in the study population, and we conducted our study only among engineering students; the result may not be conclusive to all students attending higher Ethiopian institutions. Nevertheless, our study shows the current status of mental distress among engineering students, which can be generalised to institutions of similar setups in Ethiopia and this finding may benefit the EMoH in suggesting a plan of re-evaluating higher education student deployment policy and encourages researchers to develop a robust study to improve mental distress among undergraduate engineering students.…”
Section: Discussionmentioning
confidence: 94%
“…Although mental distress affect any one numerous studies reported that high burden of mental distress found in university students compared to the other general population (3,4), despite that its burden varies considerably from nation to nation or country to country according to previous studies finding, the magnitude of mental distress at French was 25.7% in first-year university students (5), in Australian 67.4% (6), in America 82% preexisting social support (19,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%